The Influence of Digital Service Aspects on Online Purchasing Decisions: A Case Study on Shopee Users - Melinda Sari (Journal of Organizational Performance and Analysis, 2025)
The purpose of this study is to analyze the influence of Website Quality, Trust, and E-Service Quality on online purchasing decisions at the online shop shopee among students. This type of research is quantitative with a sampling technique using purposive sampling with a sample size of 246 respondents. The data was analyzed using the structural equitation modeling partial least squares (SEM-PLS) method to test the relationship between variables. The results of the study indicate that website quality, trust, e-service quality have a positive and significant influence on online purchasing decisions at the shopee online shop. These findings indicate that improving the digital quality of Shopee's services can directly drive conversion and customer loyalty. The implications of this study provide input for e-commerce players, especially Shopee, to continue to improve technical aspects and customer trust in managing online services.